. Живе питання живого життя / САЛИКОВ Р.А., КОПЫЛОВ И.Я., ЮСУПОВ Э.Ю. Национальные процессы в СССР. - М.: Наука, 1987. - 351 с. - Римаренко , Ю.І.; Вилков, Ю.С.; Щуровський, А.М. (Український історичний журнал, 1988)
.